Ultrasound-assisted amine functionalized graphene oxide for enhanced CO2 adsorption. (1st July 2019) - Liu, Yamin; Sajjadi, Baharak; Chen, Wei-Yin; Chatterjee, Riya
Graphical abstract: Highlights: An aminated GO for CO2 adsorption was prepared by a novel ultrasound-enhanced amine-functionalization method. The ultrasound irradiation was very effective in the interaction between the amine and the oxygen-containing groups of GO. The thermal resistance property of aminated GO makes it ideal candidate for CO2 adsorption from flue gas. The aminated GO exhibited a better adsorption capacity of 1.2 mmol g −1 of adsorbent in the flue gas temperature (338 K). Abstract: The present study discusses a novel ultrasound promoted amination technique to functionalize graphene oxide (GO) for CO2 adsorption. Graphene oxide was synthesized following the modified Hummer's method. The developed functionalization technique integrates the advantages of low-frequency ultrasonic physical activation with the chemical functionalization using tetraethylenepentamine (TEPA). Acoustic treatment exfoliates the clusters of graphene oxide and enhances the surface area for the subsequent amine functionalization and CO2 adsorption. Changes in textural properties, surface functionalities, thermal stability, and elemental compositions were examined before and after activation of graphene oxide. The characterization results revealed substantial increment of N content, from 0.08 in pristine to 4.84% in functionalized GO and the subsequent reduction in surface area from 289 to 198 m 2 /g in the functionalized GO, indicating attachment of TEPA to GO structure. CO2 adsorption experiments were conducted under diluted CO2 with the partial pressure of 0.10 atm. at 338 K and the results revealed that ultrasonic-TEPA activated GO possessed enhanced adsorption capacity of 1.2 mmol g −1 over pristine GO. While pristine GO could only achieve the maximum adsorption capacity of 0.3 mmol g −1 at 303 K. Besides, the sonochemically modified adsorbent showed stable cyclic adsorption-regeneration performance with only 1% reduction in adsorption capacity after 10 cycles. Finally, the effectiveness of the developed physicochemical activation technique was determined by comparing its adsorption capacity with the adsorbents found from literature.